2017
DOI: 10.7821/naer.2017.1.180
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia and Textual Reading Comprehension: Multimedia as Personal Learning Environment’s Enriching Format

Abstract: In this article we will discuss part of a piece of research that was conducted with two 4ESO groups. Textual learning is opposed to multimedia learning within the context of PLE's (Personal Learning Environment) reading tools and strategies. In the research an analysis was made of whether it would be possible to improve the reading process through multimedia over a school term in two different aspects; one evolutionary with six classroom exercises and one evaluation with a final exercise. Concretely, this arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…More specifically, Keller's model proved helpful to check the degree of motivation raised by different technological resources amongst students. Examples are: videogames [62]; the inclusion of video in e-learning learning sessions [63]; audio podcasts [64]; Massive Open Online Courses [65,66]; or AR [67][68][69].…”
Section: Information Collection Instrumentsmentioning
confidence: 99%
“…More specifically, Keller's model proved helpful to check the degree of motivation raised by different technological resources amongst students. Examples are: videogames [62]; the inclusion of video in e-learning learning sessions [63]; audio podcasts [64]; Massive Open Online Courses [65,66]; or AR [67][68][69].…”
Section: Information Collection Instrumentsmentioning
confidence: 99%
“…This theory has positive effects on reading comprehension as well. For example, while doing reading comprehension-related exercises, García, Rigo and Jiménez (2017) observed students made fewer mistakes as they focused more on these multimediabased exercises. In addition, they remembered more and learned more accurately.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study (de Leng et al, 2007) also reported that using a video-assisted clinical scenario offered medical students a more authentic, holistic, and comprehensive perspective; provided better learning flow; and helped them retain lesson materials for a longer period than using a text-assisted case scenario. Garcia et al (2017) reported that providing multimedia materials led to better comprehension and cognitive abilities in students compared with text-only materials, as multimedia materials helped reduce the amount of time students are required to process external situations cognitively and strengthened their data integration abilities. A systematic review and meta-analysis (Tudor Car et al, 2019) found that digital PBL improved health professionals' knowledge, attitudes, and satisfaction.…”
Section: Introductionmentioning
confidence: 99%